2022
DOI: 10.3389/fonc.2022.952129
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of the potential cuproptosis-related biomarker LIAS that regulates prognosis and immunotherapy of pan-cancers

Abstract: Lipoic acid synthetase (LIAS) has been demonstrated to play a crucial role in the progression of cancer. Exploring the underlying mechanisms and biological functions of LIAS could have potential therapeutic guidance for cancer treatment. Our study has explored the expression levels and prognostic values of LIAS in pan-cancer through several bioinformatics platforms, including TIMER2.0, Gene Expression Profiling Interactive Analysis, version 2 (GEPIA2.0), and Human Protein Atlas (HPA). We found that a high LIAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 35 publications
5
22
0
Order By: Relevance
“…LIAS synthesized lipoic acid by introducing two sulfhydryl groups at the C6 and C8 sites of the octanoic acid moiety, deficiency of which led to neonatal epilepsy, disorder in mitochondrial energetic metabolism and elevated glycine [ 100 ]. Similarly, LIAS expression levels tend to correlate with prognosis in different patients, high LIAS expression in lung cancer was suggested to have a poor prognosis, while in KIRC and ovarian cancer it was considered to be associated with a better prognosis [ 101 ]. LIPT1catalyzed the transfer of a lipoyl group to the lysine residue of the target enzymes [ 102 ], deficiency of which will lead to Leigh disease together with a deficiency of PDC [ 103 ].In addition, cancer cells growth and invasion were prevented by knocking down the expression of the LIPT1 gene [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…LIAS synthesized lipoic acid by introducing two sulfhydryl groups at the C6 and C8 sites of the octanoic acid moiety, deficiency of which led to neonatal epilepsy, disorder in mitochondrial energetic metabolism and elevated glycine [ 100 ]. Similarly, LIAS expression levels tend to correlate with prognosis in different patients, high LIAS expression in lung cancer was suggested to have a poor prognosis, while in KIRC and ovarian cancer it was considered to be associated with a better prognosis [ 101 ]. LIPT1catalyzed the transfer of a lipoyl group to the lysine residue of the target enzymes [ 102 ], deficiency of which will lead to Leigh disease together with a deficiency of PDC [ 103 ].In addition, cancer cells growth and invasion were prevented by knocking down the expression of the LIPT1 gene [ 104 ].…”
Section: Introductionmentioning
confidence: 99%
“…The expression of LIPT1 was positively correlated with CD8 T cells and macrophages in Uterine Corpus Endometrial Carcinoma ( 55 ). The expression of LIPT1 is associated with the infiltration of many immune cells in various cancers ( 56 ). Nevertheless, the detailed mechanism of the influences of CRGs on immune cell infiltration is unclear and deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Via PubMed, we found that these target genes play a crucial role in the prognosis and malignancy of tumors. Yuan et al showed through a comprehensive pan-cancer analysis that LIAS may have potential significance in the progression of v a r io u s c a n c e r s a n d a l s o pr e d i c t t h e e f fi c ac y o f immunotherapy in cancer patients (43). PDHB could act as regulatory targets of multiple non-coding RNAs to regulate tumor cell progression (44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%